Innovation in a Newly Industrializing Country: A Multiple Discriminant Analysis - Kim, Linsu; Kim, Youngbae (Management Science, 1985)
This article examines 42 innovative firms in a newly industrializing country, Korea. It identifies different patterns of innovation associated with four types of firms, which is categorized by two variables: the source of initiation and the local availability of related foreign products. Bivariate analyses suggest that innovation patterns are distinctly different for Type I firms (user initiated and related foreign products locally available) and Type IV firms (innovator initiated and no related foreign products locally available). Type I firms use and benefit most from close interactions with customers and visits to the domestic users of related foreign products, while Type IV firms benefit most from the overseas observation of foreign suppliers and the assistance of local R&D institutes. The other two groups are more closely related but still different from the above two groups. The results of a multiple discriminant analysis are supportive of the patterns which emerged in the bivariate analyses. It was also found that majority of important and crucial information to solve technical problems were transferred free of charge from abroad through informal mechanisms rather than formal collaboration with foreign firms. The findings suggest that different situations call for different approaches to make innovations successful.